The distribution, magnitude, and endemic species of US springs - Work, Kirsten (Frontiers in Environmental Science, 2023)
Freshwater springs and other groundwater-dependent ecosystems (GDEs) represent important natural resources in landscapes, providing consistent, high-quality water to both freshwater and terrestrial organisms. However, spring and GDE conservation does not appear to be a prominent feature on the US conservation radar. Therefore, this study evaluated the distribution and size of springs in the US with the national water dataset: the US Geological Survey National Water Information System. Using all available measurements of spring discharge and the sampling dates for all springs with data in the dataset (10,279 springs), I compared the number and sizes of springs between states and, where time series were available, determined whether the springs were maintaining historic discharges. I evaluated data quality using the date of the last sampling, number of times sampled, and the length of time sampled for each spring. Finally, I searched the literature for spring endemic species and recorded the states in which they occurred. Within the database, springs were most abundant in western states, but average discharges were largest for states in the southeast and for Idaho and Alaska. Very large springs occurred in some western states, but the multitudes of tiny springs reduced the average discharges. The data were poorly resolved as many of the springs had been sampled only once, often 40-50 years ago. Time series were available only for 126 springs and half of these springs exhibited declines in discharge. Endemic species were mentioned in the literature for 24 states, particularly those in the lower half of the country, and so loss of spring integrity would threaten biodiversity in many states. Due to the poor resolution of the data, broad conclusions about the integrity of these important freshwater systems are difficult to impossible to make for most states using the national dataset. Therefore, I call for a concerted national effort to more broadly evaluate spring and GDE resources. Springs and GDEs are likely to become even more important in the future as climate changes and their roles as freshwater refuges, temperature buffers, and bellwethers become even more important.